(untitled) (Discourse of Law and Administration, 2024)
The aim of this study is to point out and draw attention to the problems connected with the effects of contemporary legal regulations of the new technologies’ usage in administrative and administrative court proceedings on the legal situation of the professional legal representatives. Through analysis of included in the legal systems obligations to use new technologies, as well as the right to them it was possible to name main obstacles that make existing regulations defective and ineffectiveness. Differences in procedures, as well on the linguistic levels make the application of the helpful regulations too complex, what slows down progressive computerization of administration and administrative courts.